DRIF: notação para representação diagramática de fluxo de informação e comportamento informacional em processos organizacionais - Wilimar Junio Ruas (2021)
Managing the flow of information produced in organizations is one of the great challenges faced by managers. The analysis of this flow allows us to understand how information flows and how this flow can interfere in the way that organizational actors behave in the face of information. Representing the information flow plus considerations of the actors' informational behavior is an unprecedented alternative for visualizing the complexity of the information dynamics in the organizational context, aiming to understand the performance of the flow in this socio-technical system, and which still contemplates the interactions of its stakeholders. technical and social elements in the execution of work process tasks. This research aimed to create a notation, called DRIF, to represent the flow of information enriched by considerations of informational behavior in organizational processes. The scope and application context of DRIF are the processes and tasks in organizations. Due to the absence in the literature, the hypothesis was raised that it is possible to build a diagrammatic representation of information flow that considers concepts of informational behavior for processes, based on elements of notations widely disseminated as UML and BPMN. The problem was approached based on the Regulative Cycle and the Nested Problem Structure of the Design Science Research (DSR) method by Wieringa (2009, 2014), inserted in the Design Science research paradigm. Research classified as applied in nature, exploratory in terms of objectives and qualitative in terms of approach. Data collection in the DSR stages was carried out through a bibliographic survey, systematic literature review and focus group. The main contribution of this thesis is that the DRIF notation allows a vision of modeling for concepts of information science, allowing to describe "how is" the flow of information in a given process, contemplating the interactions of elements that make up the sociotechnical system of organizations. This vision of modeling the concepts contributes to the management of informational flows in processes and tasks in the work environment.